2023
DOI: 10.3390/microorganisms11051324
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of the Cell-Free Supernatant of the Lactobacillus casei Strain IMAU60214 against the Different Pathogenic Properties of Diarrheagenic Escherichia coli

Abstract: Enteroaggregative Escherichia coli (EAEC) and enterohemorrhagic E. coli (EHEC) are E. coli pathotypes associated with unmanageable diarrhea in children and adults. An alternative to the treatment of infections caused by these microorganisms is the use of the bacteria of the Lactobacillus genus; however, the beneficial effects on the intestinal mucosa are specific to the strain and species. The interest of this study consisted of analyzing the coaggregation properties of Lactobacillus casei IMAU60214, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…These studies disagreed with Yusra and Likaa (2013) who reported that in the case of B. cereus , L. plantarum MIC was 0.07 ml. Approaches of probiotics might successfully inhibit pathogens such as L. monocytogenes ( Wu et al , 2022 ), other studies stated that L. casei IMAU60214 was effective against Escherichia coli ( Rocha-Ramírez et al , 2023 ). Similarly, L. fermentum LBF433 and L. casei LBC 237 have sufficient action against Salmonella ( Lando et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies disagreed with Yusra and Likaa (2013) who reported that in the case of B. cereus , L. plantarum MIC was 0.07 ml. Approaches of probiotics might successfully inhibit pathogens such as L. monocytogenes ( Wu et al , 2022 ), other studies stated that L. casei IMAU60214 was effective against Escherichia coli ( Rocha-Ramírez et al , 2023 ). Similarly, L. fermentum LBF433 and L. casei LBC 237 have sufficient action against Salmonella ( Lando et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using cell-free culture supernatant, also called bacteria-free supernatant, fecal supernatant, or simply supernatant, has proven to be an effective way to study host-microbe, or in fact host-microbial metabolite, interactions. For example, a few studies report on the protective effect of probiotic culture supernatants against invasion of pathogenic Escherichia coli (E. coli) strains or against 5-fluorouracil (5-FU)-induced intestinal epithelial cell damage [68][69][70] . The latter study used an intestinal epithelial cell line derived from rat intestine [68] , wherefore results might be less relevant for humans, while the models that applied an E. coli challenge used either the human intestine-derived HT-29 cell line [70] or Caco-2 and T84 cell lines [69] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a few studies report on the protective effect of probiotic culture supernatants against invasion of pathogenic Escherichia coli (E. coli) strains or against 5-fluorouracil (5-FU)-induced intestinal epithelial cell damage [68][69][70] . The latter study used an intestinal epithelial cell line derived from rat intestine [68] , wherefore results might be less relevant for humans, while the models that applied an E. coli challenge used either the human intestine-derived HT-29 cell line [70] or Caco-2 and T84 cell lines [69] . One step further towards the physiological resemblance of the human intestinal tissue structure goes a Caco-2/dendritic cell co-culture model that studies the innate immune response towards a pathogenic challenge with Salmonella typhi [71] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using probiotics instead of antibiotics to regulate the intestinal microbiota of dogs is also one of the current research hotspots. A variety of Lactobacillus have killing effects on some common therapeutic bacteria, such as Escherichia coli , Staphylococcus aureus , and Salmonella enteritidis [ 39 , 40 , 41 ]. However, there are still few reports on animal experiments.…”
Section: The Function Of Probiotics and Prebiotics On Canine Intestin...mentioning
confidence: 99%